(untitled) (Applied Biological Research, 2014)
Area-specific profiling of physiological and biochemical parameters in different species is prerequisite for establishing reference values valid for clinical practice. The present study was aimed at physiological, haemato logical and biochemical profiling of domestic geese of Kashmir. The study was conducted on 30 adult domestic geese comprising of 12 male and 18 female (procured locally) which were maintained at Centre of Research on Poultry, SKUAST-Kashmir. The average body temperature, respiration rate and heart rate in geese were 40.05 ± 0.15oC, 17.16 ± 0.75 breaths min-1 and 60.57±5.09 beats min-1, respectively. Electrocardiogram (ECG) showed presence of P, QRS and T waves. The mean electrical axis/ instantaneous mean vector ranged from -86 to -95oindicating its orientation along the long axis of body and superior to frontal plane. The amplitude of QRS wave was almost similar and highest in lead II and III, whereas lead I could hardly represent voltages of QRS wave. The voltage in QRS wave ranged from 0.9 to 1.3 mv. The mean hemoglobin, ESR, PCV, TEC, MCV, MCH, MCHC and TLC was 11.5 ± 0.2 mg dL-1, 0.1 ± 0.17 mm hr-1, 50.08 ± 1.81%, 3.06 ± 0.78 x 106 mm3, 166.13 ± 5.35 m3, 38.25 ± 1.26 pg, 23.14 ± 0.50% and 67.01 ± 4.08 x 103 mm3, respectively. The differential leukocyte count revealed overall mean of 89.27±1.36, 7.77±1.30, 2.95±0.45 and 0.0% heterophils, lymphocytes, monocytes and basophils, respectively. The blood glucose, total protein, cholesterol-LS and HDL-cholesterol levels were 216.3 ±5.5 g dL-1, 21.59± 1.29 g L-1, 123.0 ±10.4 mg dL-1and 29.04 ±2.24 mg dL-1, respectively. Gender-wise, only heart rate and body temperature showed a significant difference. The present study established basic physiological and haemato-biochemical indices of Kashmir geese.